Grammatical Cohesion Found In ‘This Christmas’ Novel by Nora Roberts: Discourse Analysis - Alita Gumati Raftinia; Heri Heryono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This purpose of this study is to analyze and investigate the function and the various types of Grammatical Cohesion in the novel This Christmas by Nora Roberts. The research discusses about written text (novel) which more easily to be observed. A discourse is the unit of language formed from a series of sentences that are cohesive and coherent either written or speech. This research also observed the function and what types of grammatical cohesion in This Chirstmas novel. In grammatical cohesion there are four types such as subtitution, ellipsis, reference and conjunction. Result of the research are 10 references detected in the novel (34.4%), 6 subtitution found in the text (21%), 3 ellipsis (10,2%) and 10 conjunctions (34,4%).